DESIGN OF URBAN OBJECTS OF LANDSCAPE ARCHITECTURE - THE GREENING OF TERRITORIES - Zafarbek Matniyazov; Gulchekhra Meliboeva (Scholars Digest Publishing, 2023)
The integration of green spaces and urban objects of landscape architecture in the design of cities is an essential approach that fosters livable environments and supports urban sustainability. This paper explores the concept of urban objects of landscape architecture and the importance of greening territories in urban areas. It further investigates how the design of these urban objects and the use of green technologies contribute to the enhancement of urban environments, improving the quality of life of city residents. Furthermore, the paper highlights examples of exemplary urban design projects that effectively incorporate green spaces and landscape architecture to improve urban landscapes. The study findings highlight the importance of incorporating landscape architecture principles in urban planning and design to create sustainable, healthy, and livable cities for present and future inhabitants. The paper also discusses the importance of incorporating sustainable design practices, such as green technologies, water management systems, and urban agriculture, to further enhance the greening of territories. By implementing these innovations, cities can create environmentally friendly and comfortable spaces that improve the overall quality of life for residents.
Keywords: Urban objects, Landscape architecture, Greening, Territories, Sustainable design, Green spaces, Urban planning.